The Removal of Endo- and Enterotoxins From Bacteriophage Preparations - Hietala, Ville; Horsma-Heikkinen, Jenni; Carron, Annelie; Skurnik, Mikael; Kiljunen, Saija (Frontiers in Microbiology, 2019)
The production of phages for therapeutic purposes demands fast, efficient and scalable purification procedures. Phage lysates have a wide range of impurities, of which endotoxins of gram-negative bacteria and protein toxins produced by many pathogenic bacterial species are harmful to humans. The highest allowed endotoxin concentration for parenterally applied medicines is 5 EU/kg/h. The aim of this study was to evaluate the feasibility of different purification methods in endotoxin and protein toxin removal in the production of phage preparations for clinical use. In the purification assays, we utilized three phages: Escherichia phage vB_EcoM_fHoEco02, Acinetobacter phage vB_ApiM_fHyAci03, and Staphylococcus phage vB_SauM_fRuSau02. The purification methods tested in the study were precipitation with polyethylene glycol, ultracentrifugation, ultrafiltration, anion exchange chromatography, octanol extraction, two different endotoxin removal columns, and different combinations thereof. The efficiency of the applied purification protocols was evaluated by measuring phage titer and either endotoxins or staphylococcal enterotoxins A and C (SEA and SEC, respectively) from samples taken from different purification steps. The most efficient procedure in endotoxin removal was the combination of ultrafiltration and EndoTrap HD affinity column, which was able to reduce the endotoxin-to-phage ratio of vB_EcoM_fHoEco02 lysate from 3.5×104 Endotoxin Units (EU)/109 plaque forming units (PFU) to 0.09 EU/109 PFU. The combination of ultrafiltration and anion exchange chromatography resulted in ratio 96 EU/109 PFU, and the addition of octanol extraction step into this procedure still reduced this ratio threefold. The other methods tested either resulted to less efficient endotoxin removal or required the use of harmful chemicals that should be avoided when producing phage preparations for medical use. Ultrafiltration with 100,000 MWCO efficiently removed enterotoxins from vB_SauM_fRuSau02 lysate (from 1.3 to 0.06 ng SEA/109 PFU), and anion exchange chromatography reduced the enterotoxin concentration below 0.25 ng/ml, the detection limit of the assay.